Effect of a Nutraceutical Combination on Oxidative Stress Biomarkers in Healthy Subjects and Patients with Alzheimer's Disease. - Jastrząb, Rafał; Małecki, Andrzej; Kmiecik-Małecka, Elżbieta; Gorzkowska, Agnieszka; Kubas, Kamil; Widłak-Kargul, Justyna; Wolman, Damian; Matkiewicz, Katarzyna; Nowacka-Chmielewska, Marta; Liśkiewicz, Daniela; Grabowska, Konstancja; Grabowski, Mateusz; et al. (Nutrients, 2026)
Background/Objectives: Advanced glycation end products (AGEs) and oxidative stress increase with aging and are implicated in Alzheimer's disease (AD). We developed an anti-glycation blend using LC-MS-based screening and assessed its effects on oxidative and glycation-related biomarkers in humans. Methods: Twelve candidate compounds were screened in a BSA–glucose model using LC-MS peptide mapping to quantify lysine glycation and rank inhibitory activity. The top candidates were combined into a three-compound blend (quercetin, rutin, genistein). In a randomized, double-blind, placebo-controlled 3-month trial, older healthy adults (n = 30) and individuals with AD (n = 30) received anti-AGE blend (n = 15 in older group and n = 15 in AD group) or placebo (n = 15 in older group and n = 15 in AD group). Serum malondialdehyde and urinary Nε-(carboxymethyl)lysine were measured pre–post intervention. Pre/post and between-arm comparisons within each population were performed using REML ANOVA with Tukey post hoc tests. Serum MDA (malondialdehyde) and urinary CML (Nε-(carboxymethyl)lysine) were prespecified biomarker outcomes and are reported here as co-primary biomarker endpoints. No formal a priori sample size calculation was performed; the study size was feasibility-based. Results: LC-MS screening identified genistein, quercetin, and rutin as the most consistent inhibitors of glucose-driven BSA glycation. In older healthy adults, serum MDA decreased after anti-AGE supplementation (p < 0.001) and differed from the placebo (p < 0.01), while no change was observed within the placebo group (ns). In the AD cohort, MDA did not change significantly from baseline within either arm (ns), but post-intervention MDA was lower in anti-AGE than in the placebo (p < 0.05). Urinary CML was unchanged in older healthy adults (ns in both arms), whereas in AD, it decreased after anti-AGE supplementation (p < 0.01) and differed from the placebo (p < 0.05). Conclusions: A screening-guided anti-glycation blend supplementation was associated with changes in selected biomarkers in humans: MDA decreased across cohorts, while CML decreased selectively in AD. Larger trials with extended biomarker panels and LC–MS/MS confirmation are warranted.